Downregulation of GLYAT Facilitates Tumor Growth and Metastasis and Poor Clinical Outcomes Through the PI3K/AKT/Snail Pathway in Human Breast Cancer - Tian, Xin; Wu, Lina; Jiang, Min; Zhang, Zhenyong; Wu, Rong; Miao, Jianing; Liu, Caigang; Gao, Song (Frontiers in Oncology, 2021)
Background: The Glycine N-acyltransferase (GLYAT) gene encodes a protein that catalyzes the transfer of acyl groups from acyl CoA to glycine, resulting in acyl glycine and coenzyme A. Aberrant GLYAT expression is associated with several malignant tumors, but its clinical importance in malignant tumors, especially human breast cancer (BC), has yet to be fully addressed. This study aims to evaluate the clinical function of GLYAT in BC patients. Methods: GLYAT expression was determined by immune blot and immunohistochemistry in three BC cell lines and primary cancer tissues. The MDA-MB 231 cell line was used for GLYAT gene knockdown experiments while the MCF7 cell line for overexpression experiments. Colony formation experiments, soft agar experiments, and transwell assays were utilized for further inspection of cell migration and proliferation capabilities. Immunofluorescence and western blot were used to detect markers of the epithelial-mesenchymal transition (EMT) and changes in the PI3K/AKT/Snail pathway. The role of GLYAT in tumor growth and metastasis was also assessed in nude mice in vivo. Also, a correlation analysis was performed between clinicopathological features and GLYAT expression in BC patients. Results: GLYAT was decreased in human BC tissues and cell lines. Functional analysis showed that knockdown of GLYAT augmented BC cell proliferation in vitro and in vivo. However, this phenomenon was reversed when GLYAT was overexpressed in the transfected cells. Moreover, GLYAT inhibited the migratory properties of BC cells, likely through the activation of PI3K/AKT/Snail signaling, which subsequently induced the EMT. IHC analysis indicated that GLYAT was decreased in human BC tissues and lower GLYAT expression was correlated with histological grade, tumor TNM stage, Ki-67 status, and poorer survival in BC patients. Furthermore, lower GLYAT expression seemed as an independent risk factor related to poor prognosis in BC patients based on Cox regression analyses. Conclusion: Our findings demonstrate that downregulation of GLYAT expression in human breast cancer is correlated with EMT via the PI3K/AKT/Snail pathway and is also associated with histological grade, tumor TNM stage, Ki-67 status, and poor survival in breast cancer patients.